Representasi Konflik Ekonomi dalam Film Agak Laen: Analisis Semiotika Roland Barthes - Azmi, Mohammad Ardya Noor; Wibowo, Arif Ardy (Jurnal Dinamika Ilmu Komunikasi, 2025)
The film Agak Laen (2024) achieved remarkable commercial success with 9.13 million viewers by blending humor with portrayals of unemployment, poverty, and socioeconomic inequality that mirror contemporary Indonesian realities. This study analyzes the representation of economic conflict and the underlying ideology embedded in the film’s narrative using Roland Barthes’ semiotic approach. Employing a qualitative descriptive method, data were collected through documentation, literature review, and scene observation. Analysis of seven representative scenes through Barthes’ three levels of meaning—denotative, connotative, and mythical—reveals the coexistence of contradictory economic myths. The film simultaneously naturalizes structural inequality through the myths “every job is a blessing” and “entrepreneurship as a universal solution,” while critiquing contemporary economic exploitation through “viral equals success” and “entertainment is innocent.” The findings demonstrate that popular cinema operates as a contested ideological terrain that both reproduces and challenges structural inequality. Practically, this study underscores the importance of critical media literacy and the potential of cinema as a pedagogical medium for fostering reflective and transformative understanding of economic realities.